Developing policies for the end-of-life of energy infrastructure: Coming to terms with the challenges of decommissioning. (September 2020) - Invernizzi, Diletta Colette; Locatelli, Giorgio; Velenturf, Anne; Love, Peter ED.; Purnell, Phil; Brookes, Naomi J.
Abstract: Energy sector policies have focused historically on the planning, design and construction of energy infrastructures, while typically overlooking the processes required for the management of their end-of-life, and particularly their decommissioning. However, decommissioning of existing and future energy infrastructures is constrained by a plethora of technical, economic, social and environmental challenges that must be understood and addressed if such infrastructures are to make a net-positive contribution over their whole life. Here, we introduce the magnitude and variety of these challenges to raise awareness and stimulate debate on the development of reasonable policies for current and future decommissioning projects. Focusing on power plants, the paper provides the foundations for the interdisciplinary thinking required to deliver an integrated decommissioning policy that incorporates circular economy principles to maximise value throughout the lifecycle of energy infrastructures. We conclude by suggesting new research paths that will promote more sustainable management of energy infrastructures at the end of their life. Highlights: Historically, energy policy has focused on planning and delivering new infrastructures. Many energy infrastructures are now reaching the end of their life. We provide an overview of these infrastructures and their decommissioning challenges. Infrastructure designers must consider decommissioning to enhance resource recovery. Sustainable decommissioning policies must integrate circular economy principles.